2015
DOI: 10.1039/c5ob00030k
|View full text |Cite
|
Sign up to set email alerts
|

3-Nitro-2-pyridinesulfenyl-mediated solid-phase disulfide ligation in the synthesis of disulfide bond-containing cyclic peptides

Abstract: A new solid-phase disulfide ligation method is developed to prepare a disulfide peptide from two types of Cys-containing peptide fragments with minimum purification steps. In combination with the subsequent intramolecular amide bond formation, a cyclic nonapeptide, oxytocin, was efficiently synthesized as a fundamental model for more complex cyclic peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Npys‐OMe 3 a is a stable yellow crystalline compound, which can be stored under shelf conditions for at least six months ( 1 H NMR spectra and Figure S1 in the Supporting Information). In addition, as shown in Scheme B, by using solid‐phase supported Npys‐OMe ( 5 ), 6‐(benzylthio)‐5‐nitronicotinyl ( 4 ) was synthesized on a resin based on a polyethylene glycol ChemMatrix ® resin with swelling properties in both aqueous and organic solvents, and treated with 2 % (v/v) SO 2 Cl 2 /1,2‐DCE in the presence of pyridine to activate the resin‐bound compound as its sulfenyl chloride. Then, after the resin was washed with ice‐cooled CH 2 Cl 2 and dried under a gentle stream of N 2 , it was mixed with 30 % (v/v) DIPEA/MeOH and stirred by vortex mixing for 1.5 h and then filtered and washed with CH 2 Cl 2 and MeOH (five and three times, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Npys‐OMe 3 a is a stable yellow crystalline compound, which can be stored under shelf conditions for at least six months ( 1 H NMR spectra and Figure S1 in the Supporting Information). In addition, as shown in Scheme B, by using solid‐phase supported Npys‐OMe ( 5 ), 6‐(benzylthio)‐5‐nitronicotinyl ( 4 ) was synthesized on a resin based on a polyethylene glycol ChemMatrix ® resin with swelling properties in both aqueous and organic solvents, and treated with 2 % (v/v) SO 2 Cl 2 /1,2‐DCE in the presence of pyridine to activate the resin‐bound compound as its sulfenyl chloride. Then, after the resin was washed with ice‐cooled CH 2 Cl 2 and dried under a gentle stream of N 2 , it was mixed with 30 % (v/v) DIPEA/MeOH and stirred by vortex mixing for 1.5 h and then filtered and washed with CH 2 Cl 2 and MeOH (five and three times, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…This affords au seful strategy for the synthesis of peptides containing multiple disulfides. [19] In our efforts to develop innovativeN pys chemistry, [20,21] directed towards disulfide bond formation, we were interested in ac ategory of the Npys derivatives, 3-nitro-2-pyridinesulfenate alkoxides (Npys-OR). As originally reported by Matsueda et al, [22] these are prepared by coupling Npys-Cl with various alcohols in the presence of ab ase.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, sulfide derivative 6 was reacted in acetonitrile with activated solid-supported disulfide coupling reagent 7, which was prepared from its benzylsulfide form with 2% sulfuryl chloride in 1,2-dichloroethane. 25 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 It has been reported that the Z33 peptide has a propensity to form an α-helix and bind to the Fc-region of human IgG 1 by the helix-loop-helix structure 17, 27 ( Figure S1). In the circular dichroism (CD) spectra of synthesized compounds, peptide 9 with an additional Cys-Gly sequence at the N-terminus shows almost the same spectral pattern with an α-helix as 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34...…”
Section: Resultsmentioning
confidence: 99%
“…This reaction was performed on the basis of the previous reaction conditions. 25 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 24 A375 cells were cultured in DMEM containing 10% FBS. Herceptin resistant SKBR-3 cells were cultured in McCoy's 5A containing 10% FBS and 8 µg/mL of Herceptin.…”
Section: Synthesis Of Hybrid Molecule 10 (Plinabulin-ss-z33) By a Solmentioning
confidence: 99%
“…These latest developments around solid phase reagents led to the synthesis of a universal disulfide bond formation reagent that proved to be particularly useful for disulfide formation in peptides . After chlorosulfenylation, the aforementioned benzylsulfide Npys resin reacted with a tert ‐butyl‐protected thiol‐containing peptide A to form the corresponding active disulfide.…”
Section: Introductionmentioning
confidence: 99%